The Covid-19 Pandemic and Economy – A Study on Bangladesh - Fariba Azizzadeh; S. M. Basir; Mohammad Shahidul Islam; Muhammad Ali (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2 puts serious threats to mankind and the economy across the globe. Bangladesh experienced the 1st wave of attack with the detection of 3 active cases on 08 March 2020, with the first fatality on 18 March 2020. The country could keep the death toll to the minimum and economic wheel moving compared to other affected countries. However, despite the vaccination drive launched on 07 February 2021 and the normal economic progression saw light, the sudden spike of affected and death cases from the 1st week of March 2021 and its subsequent upsurge breaking all previous records made questionable the overall strategies/measures of the country. Therefore, this study mainly endeavours to outline strategies/measures to effectively combat the COVID-19 pandemic maintaining a needed balance between the country’s economic progression and the death toll.